Focused psychosocial interventions for children in low-resource humanitarian settings: a systematic review and individual participant data meta-analysis - Marianna Purgato, PhD; Alden L Gross, PhD; Theresa Betancourt, ScD; Paul Bolton, MBBS; Chiara Bonetto, PhD; Chiara Gastaldon, MD; James Gordon, MD; Paul O'Callaghan, PhD; Davide Papola, MD; Kirsi Peltonen, PhD; Raija-Leena Punamaki, ProfPhD; Justin Richards, PhD; et al. (Elsevier, 2018)
Summary: Background: Results from studies evaluating the effectiveness of focused psychosocial support interventions in children exposed to traumatic events in humanitarian settings in low-income and middle-income countries have been inconsistent, showing varying results by setting and subgroup (eg, age or gender). We aimed to assess the effectiveness of these interventions, and to explore which children are likely to benefit most. Methods: We did a systematic review and meta-analysis of individual participant data (IPD) from 3143 children recruited to 11 randomised controlled trials of focused psychosocial support interventions versus waiting list. We searched the Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, PsycArticles, Web of Science, and the main local low-income and middle-income countries (LMICs) databases according to the list of databases relevant to LMIC developed collaboratively by Cochrane and WHO Library, up to November, 2016. We included randomised controlled trials that assessed the effectiveness of focused psychosocial support interventions in children exposed to traumatic events in LMICs, compared with waiting lists (eg, inactive controls). We excluded quasi-randomised trials, studies that did not focus on psychosocial support interventions, and studies that compared two active interventions without control conditions. We requested anonymised data from each trial for each of the prespecified variables for each child who was randomly assigned. The main outcomes considered were continuous scores in post-traumatic stress disorder (PTSD) symptoms, depressive symptoms, and anxiety symptoms assessed with rating scales administered immediately (0-4 weeks) after the intervention. We harmonised all individual items from rating scales using item response theory methods. This study is registered with PROSPERO, number CRD42013006960. Findings: We identified a beneficial effect of focused psychosocial support interventions on PTSD symptoms (standardised mean difference [SMD] −0·33, 95% CI −0·52 to −0·14) that was maintained at follow-up (-0·21, −0·42 to −0·01). We also identified benefits at the endpoint for functional impairment (-0·29, −0·43 to −0·15) and for strengths: coping (-0·22, −0·43 to −0·02), hope (-0·29, −0·48 to −0·09), and social support (-0·27, −0·52 to −0·02). In IPD meta-analyses focused on age, gender, displacement status, region, and household size we found a stronger improvement in PTSD symptoms in children aged 15-18 years (-0·43, −0·63 to −0·23), in non-displaced children (-0·40, −0·52 to −0·27), and in children living in smaller households (<6 members; −0·27, −0·42 to −0·11). Interpretation: Overall, focused psychosocial interventions are effective in reducing PTSD and functional impairment, and in increasing hope, coping, and social support. Future studies should focus on strengthening interventions for younger children, displaced children, and children living in larger households. Funding: European Commission FP7th Framework Programme for Research (Marie Curie International Outgoing Fellowship) and the National Institute on Aging.